Ultrasonographic detection of fetal sexing in nanny goat - Eman H. Lazim; Barra D. Al-Watar (Iraqi Journal of Veterinary Sciences)
We aimed to evaluate the accuracy of early fetal sexing by sonography in nanny goats during three periods of gestation and their correlation with the number of fetuses. A total of 50 pregnant nanny goats were included in this study. The B mode of real-time scanner with 3.5-5 MHz transabdominal transducer was used to identify the fetal external genital organs and to evaluate the relative placement of genital tubercle (G.T.) within three different periods were the first period at 45-55 days of pregnancy, the second period at 55-56 days of pregnancy, and the third period at 65-75 days of pregnancy. The result showed that, in the signal fetus cases, the accuracy of fetal sexing was more accurate in the second period of pregnancy (62.5%) than that recorded in the 1st (56.5%) and third (40%) periods of pregnancy. The results in twine fetus cases showed that the accuracy of fetal sexing was more accurate in the first period of pregnancy (34.7%) than that recorded in the 2nd (27%) and third (20%) periods of pregnancy. The results also showed that, in triple fetus cases, the accuracy of fetal sexing was more accurate in the 1st period of pregnancy (26%) than that recorded in the 2nd (15.4%) and 3rd (6.7%) periods of pregnancy. The results of the fetal sex determination showed that a total of 15 male fetuses were accurately detected, with three fetuses wrongly detected. Similarly, a total of 11 female fetuses were accurately diagnosed, and four fetuses were incorrectly detected. The sensitivity of fetal sex determination was 78.94%, and the gender detection accuracy, sensitivity, specificity, positive predictive value, and negative predictive value were 78.78, 78.57, 83.33, and 73.33%, respectively. We conclude that the transabdominal transducer at B mode used in the 2nd period (55-56 days) of pregnancy was highly accurate for early fetal sex determination. Also, it is the best way to determine the number of fetuses in small ruminants.